91.7k views
4 votes
2(x + 3) + 2x = 3x + 12

User Malcolm
by
4.7k points

1 Answer

2 votes

We can proceed as follows to solve this equation:


2(x+3)+2x=3x+12

1. Apply the distributive property on the left side of the equation:


2\cdot x+2\cdot3+2x=3x+12

Then, we have:


2x+6+2x=3x+12

2. Add the like terms on the left side of the equation:


2x+2x+6=3x+12\Rightarrow4x+6=3x+12

3. Subtract 3x to both sides of the equation:


4x-3x+6=3x-3x+12\Rightarrow x+6=12

4. Subtract 6 from both sides of the equation:


x+6-6=12-6\Rightarrow x=6

Therefore, the value for x in the equation is equal to 6 (x = 6).

We can check this using the original equation:


2\cdot(x+3)+2x=3x+12\Rightarrow2\cdot(6+3)+2\cdot(6)=3\cdot(6)+12

Then, we have:


2\cdot(9)+12=18+12\Rightarrow18+12=18+12\Rightarrow30=30

As we can see, this is always TRUE. Therefore, the solution x = 6 is correct.

User Muminers
by
4.9k points